Guidelines from the industry 4.0 to the education 4.0: case technology IoT (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2022)
The Industry 4.0 technologies in the university environment open up new possibilities for applications and services, leading to scientific innovations in the teaching-learning process that facilitate the arrival of Education 4.0. In this article, a route is structured in the direction of higher education to consolidate efforts in the training of suitable engineers to face the challenges of Industry 4.0, consisting of: new courses in engineering programs, qualifications and skills among which stand out soft skills, and learning factories as a link between the Academy to real projects in the industry. Additionally, the Internet of Things is addressed as one of the key technologies for the scope of Education 4.0, in which its application leads to the improvement of teaching- learning process, and to the monitoring of health and emotions of the students.
Keywords: Curriculum; education 4.0; industry 4.0; engineering; IoT